Agents anywhere (AA) : uma linguagem para o desenvolvimento de aplicações multiagentes ubíquas - Escobar, Mauricio da Silva (2013)
In recent years, much research and development effort has been directed towards the fields of ubiquitous computing and multi-agent systems. Further progress is needed for taking full advantage of such technologies in order to provide a degree of intelligence, flexibility, and abstraction in building ubiquitous applications. This work presents the design of a programming language for the development of ubiquitous multi-agent applications. The language aims to define ubiquitous concepts at the same level of abstraction as multi-agent systems concepts, where important ubiquity concepts such as locations and devices are first-class abstractions. The design of the language was based on FAML, a generic meta-model for MAS development, and also draws upon some of the fundamental features of agent-oriented programming languages.